Removal and photocatalysis of 4-Nitrophenol using metallophthalocyanines - Marais, Eloïse Ann (Rhodes University, Faculty of Science, Department of Chemistry, 2008)
Photodegradation of 4-nitrophenol (4-Np) in the presence of water-soluble zinc phthalocyanines and water-insoluble metallophthalocyanines is reported. The water-soluble phthalocyanines employed include zinc tetrasulphophthalocyanine (ZnPcS[subscript 4]), zinc octacarboxyphthalocyanine (ZnPc(COOH)[subscript 8]) and a sulphonated ZnPc containing a mixture of differently sulphonated derivatives (ZnPcS[subscript mix]), while the water-insoluble phthalocyanines used include unsubstituted magnesium (MgPc), zinc (ZnPc) and chloroaluminium (ClAlPc) phthalocyanine complexes and the ring-substituted zinc tetranitro (ZnPc(NO[subscript 2])[subscript 4]), zinc tetraamino (ZnPc(NH[subscript 2])[subscript 4]), zinc hexadecafluoro (ZnPcF[subscript 16]) and zinc hexadecachloro (ZnPcCl[subscript 16]) phthalocyanines. The most effective water-soluble photocatalyst is ZnPcS[subscript mix] in terms of the high quantum yield obtained for 4-Np degradation (Φ[subscript 4-Np]) as well as its photostability. While ZnPc(COOH)[subscript 8] has the highest Φ[subscript 4-Np] value relative to the other water-soluble complexes, it degrades readily during photocatalysis. The Φ[subscript 4-Np] values were closely related to the singlet oxygen quantum yields Φ[subscript Δ] and hence aggregation. The rate constants for the reaction with 4-Np were kr = 0.67 x 10[superscript 6] mol[superscript -1] dm[superscript 3] s[superscript -1] for ZnPcS[subscript mix] and 7.7 x 10[superscript 6] mol[superscript -1] dm[superscript 3] s[superscript -1] for ZnPc(COOH)[subscript 8]. ClAlPc is the most effective photocatalyst relative to the other heterogeneous photocatalysts for the phototransformation of 4-Np, with 89 ± 8.4 % degradation of 4-Np achieved after 100 min. The least effective catalysts were ZnPcCl[subscript 16] and MgPc. The final products of the photocatalysis of 4-Np in the presence of the homogeneous photocatalysts include 4-nitrocatechol and hydroquinone, while degradation of 4-Np in the presence of the heterogeneous photocatalysts resulted in fumaric acid and 4-nitrocatechol. ClAlPc was employed for the heterogeneous photocatalysis of the non-systemic insecticide, methyl paraoxon. Complete degradation of the pesticide was confirmed by the disappearance of the HPLC trace for methyl paraoxon after 100 min of irradiation with visible light. The removal of 4-Np from an aqueous medium using commercially available Amberlite[superscript ®] IRA-900 modified with metal phthalocyanines was also investigated. The metallophthalocyanines immobilised onto the surface of Amberlite[superscript ®] IRA-900 include Fe (FePcS[subscript 4]), Co (CoPcS[subscript 4]) and Ni (NiPcS[subscript 4]) tetrasulphophthalocyanines, and differently sulphonated phthalocyanine mixtures of Fe (FePcS[subscript mix]), Co (CoPcS[subscript mix]) and Ni (NiPcS[subscript mix]). Adsorption rates were fastest for the modified adsorbents at pH 9. Using the Langmuir-Hinshelwood kinetic model, the complexes showed the following order of 4-Np adsorption: CoPcS[subscript mix] > NiPcS[subscript 4] > NiPcS[subscript mix] > FePcS[subscript 4] > FePcS[subscript mix] > CoPcS[subscript 4]. The adsorbents were regenerated using dilute HNO[subscript 3], with 76 % (7.6 x 10[superscript -5] mol) of 4-Np recovered within 150 min.
Keywords: Photocatalysis; Catalysis; Electrochemistry; Nitrophenols; Phthalocyanines